RESEARCH ON THERMAL FATIGUE LIFE OF SOLDER JOINTS FOR AIRBORNE ELECTRONIC EQUIPMENT - CU QiangYi; LIU ZhiHu; TIAN Feng; ZHANG FengHua; ZHAO Gang; WU Bo (Jixie qiangdu)
Aiming at the problem of thermal fatigue of solder joints for airborne electronic equipment, the evaluation method of thermal fatigue life of solder joints suitable for engineering application was studied, considered that the empirical equation based on strain energy was suitable for multiple components on PCBA. The accelerated test method of thermal fatigue life of solder joints was discussed, the accelerated test case proved that the test was feasible, and the simulation was credible. The results indicated that the simulation and accelerated test method of thermal fatigue life of solder joints were suitable for engineering application.